The Factors Impacting Decision-Making for Breast Reconstruction in Women Following Mastectomy: A Cross-Sectional Study - Azam, Zaini; Gul, Shandan; Jan, Maria Mir; Tariq, Maham; Saleema, Aqsa; Naqvi, Syeda Rifaat Qamar; Akram, Zohra Jabeen (Journal of Gandhara Medical and Dental Science, 2024)
OBJECTIVES This study aimed to assess the Factors Impacting Decision-Making for Breast Reconstruction in Women Following Mastectomy in Combined Military Hospital, Rawalpindi METHODOLOGY This prospective cross-sectional study was conducted at a specialized Breast Clinic in the Combined Military Hospital Rawalpindi from January to June 2023. The sampling technique was non-probability sampling. A total of 56 female patients between the ages of 20-70 years with a histological diagnosis of carcinoma breast and undergoing mastectomy as part of their breast cancer therapy were included in the study. Patients who had metastatic cancer or connective tissue disorder were excluded from the study. After getting informed written consent, data was collected from patients. A semi-structured questionnaire was used as a study tool. Data was presented in the form of tables. RESULTS The surgical preference of 56 patients was studied. Only 11(19.6%) patients opted for breast reconstruction. A total of 45(80.4%) patients refused to undergo BR. Several factors affecting the decision not to have BR were identified. They included fear of recurrence in 07 (15.5%) patients, long surgical procedures in 06 (13.3%), lack of concern regarding body image in 11(24.4%), financial issues in 13 (28.8%) patients, unsatisfactory results of breast reconstruction in 8 (17.7%) patients who had lack of trust in plastic surgeon regarding their post reconstruction breast shape. CONCLUSION This study laid the conceptual groundwork that factors like fear of recurrence, long surgical procedures, disregard for body image, poverty, and plastic surgeon distrust negatively influence the likelihood of having post-mastectomy breast reconstruction (PMBR). Methods: From January 2023 to June 2023, this cross-sectional study, carried out at a specialized Breast Clinic in the Combined Military Hospital Rawalpindi, sought to explore surgical preferences for breast reconstruction (BR) among breast carcinoma patients undergoing mastectomy and to identify factors influencing these decisions. 42 patients in all were enrolled, 8 of them selected breast reconstruction while 34 did not. The decision-making process was influenced by a number of issues, such as worry about recurrence, worries about time-consuming surgical procedures, and disregard for body image, financial limitations, and previous unsuccessful reconstructive results. Results: 28 patients had right-sided disease, 13 had left-sided cancer, and 1 had bilateral involvement, according to disease features. Furthermore, 25 individuals had N0 disease, while 17 had N1 disease, according to nodal staging. Six patients had sentinel lymph node biopsy (SLNB), two underwent axillary lymph node dissection (ALND), five chose upfront surgery, and three underwent neoadjuvant therapy before surgery, demonstrating the range of the surgical methods used. Conclusion: This study provides insightful information about the complex decision-making process involving breast reconstruction in individuals with breast cancer. The identified characteristics give healthcare professionals a framework on which to build strategies that guarantee patients receive educated and individualized care, thereby improving patient happiness and quality of life in general. Key words: breast, tumor, surgery, lymph node, reconstruction, aesthetic